Variasi Model Pembelajaran Pada Siswa Di Sekolah Dasar - Hadzami, Salsabila; Maknun, Lu’luil (STAI Asy-Syukriyyah, 2022)
The purpose of this article is to outline the different types of current learning methods that are appropriate for pupils.. The learning model is a framework that offers a systematic explanation of how to conduct learning so that students may understand the precise objectives to be met. Research of this kind use descriptive qualitative methods.This article has several learning models. 1) Theory Based Learning Model, 2) Make-A-Match Learning Model, 3) Quantum Learning Model, 4) Value Clarification Technique (VCT) Learning Model, 5) Learning Based Learning Model, 6) STEAM Learning Methodology, 7) Model Peer Tutor Learning, 8) Contextual Learning Model, 9) Number Head Together Learning Model, 10) Active Knowledge Sharing Learning Model, 11) CORE Learning Model, 12) CSCL Learning Model, 13) Jigsaw Type Collaborative Learning Model. The learning model is also a learning design orIn order to implement learning effectively and efficiently, a process based on learning demands, objectives, and delivery methods must be used. This is done by reducing the learning-related challenges that students experience. This will serve as a reference for establishing yourself as a disciplined